PENGARUH PELAKSANAAN KEBIJAKAN DANA DESA TERHADAP KESEJAHTERAAN MASYARAKAT MELALUI PEMBERDAYAAN MASYARAKAT: STUDI KASUS DI KECAMATAN SIANTAR NARUMONDA KABUPATEN TOBA - Siagian, Nalom; Manalu, Darma; Tobing, Artha Lumban (Buletin Studi Ekonomi; VOL.26.NO.2.AGUSTUS 2021DO - 10.24843/BSE.2021.v26.i02.p01, 2021)
The purpose of this study was to analyze the effect of implementing rural fund policies and community empowerment on community welfare. This research was conducted in 14 (fourteen) villages scattered in Siantar Narumonda District, Toba Regency. The number of respondents in this study were 220 people who were taken using the proportional random sampling method. The data collected in this study were analyzed using structural equation model. Based on the results of the analysis, concluded that directly, the implementation of the rural fund policy has a significant positive effect on community empowerment. The implementation of the rural fund policy has a negative and insignificant effect on community welfare, while community empowerment has a significant positive effect on community welfare. Indirectly, the implementation of the rural fund policy has a significant positive effect on community welfare through community empowerment.